2006
DOI: 10.3904/kjim.2006.21.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Hemobilia from Ruptured Hepatic Artery Aneurysm in Polyarteritis Nodosa

Abstract: Hemobilia, in patients with the diagnosis of polyarteritis nodosa, is rare at clinical presentation and has a grave prognosis. We describe a case of massive hemobilia, due to aneurysmal rupture, in a patient with polyarteritis nodosa. A 39-year-old man was admitted to the hospital with upper abdominal pain. The patient had a history of partial small bowel resection, for intestinal infarction, about 5 years prior to this presentation. Abdominal computed tomography demonstrated multiple high attenuation areas in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…After identifying 671 articles, 153 articles involving 171 cases were eligible: 104 viral infection and 67 rheumatic disease AAC patients. [8,11–162] Viral infection types included: Epstein Barr virus, hepatitis virus, dengue virus, SARS-CoV-2 (COVID-19), human immunodeficiency virus, and cytomegalovirus. Rheumatic diseases included: systemic lupus erythematosus, adult-onset Still disease, Henoch-Schönlein purpura, polyarteritis nodosa, Churg-Strauss syndrome (eosinophilic granulomatosis with polyangiitis), microscopic polyangiitis, temporal arteritis, Wegener granulomatosis (granulomatosis with polyangiitis), Kawasaki syndrome, systemic juvenile idiopathic arthritis, and juvenile dermatomyositis (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…After identifying 671 articles, 153 articles involving 171 cases were eligible: 104 viral infection and 67 rheumatic disease AAC patients. [8,11–162] Viral infection types included: Epstein Barr virus, hepatitis virus, dengue virus, SARS-CoV-2 (COVID-19), human immunodeficiency virus, and cytomegalovirus. Rheumatic diseases included: systemic lupus erythematosus, adult-onset Still disease, Henoch-Schönlein purpura, polyarteritis nodosa, Churg-Strauss syndrome (eosinophilic granulomatosis with polyangiitis), microscopic polyangiitis, temporal arteritis, Wegener granulomatosis (granulomatosis with polyangiitis), Kawasaki syndrome, systemic juvenile idiopathic arthritis, and juvenile dermatomyositis (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Unless there is a history of trauma or injury, hemobilia is not easy to recognize in the early stage. [3][4][5] Of the available modalities, ERCP has played a significant role in the diagnosis and treatment of hemobilia. The purpose of this study was to analyze 37 cases of non-iatrogenic hemobilia, which were all confirmed by ERCP in our hospital, to identify the etiology and clinical manifestations of hemobilia, and to present the role for endoscopic management of hemobilia.…”
Section: Introductionmentioning
confidence: 99%
“…It is most commonly a result of rupture of a pseudoaneurysm that has formed following biliary injury at cholecystectomy, 1 but can also form following major hepatic, biliary or pancreatic operations, 2 following blunt or penetrating trauma, 3 or rarely due to inflammatory processes. [4][5][6][7] Patients with a ruptured hepatic artery aneurysm usually present with right upper quadrant pain and jaundice and haemodynamic instability, or simply can have a transaminitis. 8,9 Management of hepatic artery aneurysms includes interventional radiological procedures, such as embolization and stenting, as well as operative resection with or without vascular reconstruction.…”
mentioning
confidence: 99%
“…Rupture of a hepatic arterial aneurysm into the biliary tree is a rare cause of haemobilia. It is most commonly a result of rupture of a pseudoaneurysm that has formed following biliary injury at cholecystectomy, but can also form following major hepatic, biliary or pancreatic operations, following blunt or penetrating trauma, or rarely due to inflammatory processes . Patients with a ruptured hepatic artery aneurysm usually present with right upper quadrant pain and jaundice and haemodynamic instability, or simply can have a transaminitis …”
mentioning
confidence: 99%